Corrosion of mild steel at the seawater/sediments interface: Mechanisms and kinetics. (January 2018) - Refait, Ph.; Grolleau, A.-M.; Jeannin, M.; François, E.; Sabot, R.
Highlights: Iron sulfide and green rust compounds are formed on steel in marine sediments. Four GR compounds are identified as corrosion products of mild steel in marine mud. The various GR compounds are indicators of local variations of medium composition. Local corrosion rates as high as 140 μm yr −1 are observed in the mud zone. Abstract: Corrosion product layers formed on mild steel coupons after 6 years of permanent immersion at shallow depth in marine sediments were characterized by X-ray diffraction and μ-Raman spectroscopy. They proved mainly composed of FeS which testifies for an intense sulfate-reducing bacteria activity. Other identified compounds were siderite FeCO3 and four varieties of green rust associated with local variations of composition of the environment. The corrosion rates determined by residual thickness measurements were higher on the lower half of the coupons (average 40 μm/yr, local maximum 140 μm/yr) and smaller on the upper half, suggesting that differential aeration effects took place.